Clinical microbeam radiation therapy with a compact source: specifications of the line-focus X-ray tube - Winter, Johanna; Galek, Marek; Matejcek, Christoph; Wilkens, Jan J.; Aulenbacher, Kurt; Combs, Stephanie E.; Bartzsch, Stefan (Physics and Imaging in Radiation Oncology, 2020)
Background and purpose: Microbeam radiotherapy (MRT) is a preclinical concept in radiation oncology with arrays of alternating micrometer-wide high-dose peaks and low-dose valleys. Experiments demonstrated a superior normal tissue sparing at similar tumor control rates with MRT compared to conventional radiotherapy. Possible clinical applications are currently limited to large third-generation synchrotrons. Here, we investigated the line-focus X-ray tube as an alternative microbeam source. Materials and methods: We developed a concept for a high-voltage supply and an electron source. In Monte Carlo simulations, we assessed the influence of X-ray spectrum, focal spot size, electron incidence angle, and photon emission angle on the microbeam dose distribution. We further assessed the dose distribution of microbeam arc therapy and suggested to interpret this complex dose distribution by equivalent uniform dose. Results: An adapted modular multi-level converter can supply high-voltage powers in the megawatt range for a few seconds. The electron source with a thermionic cathode and a quadrupole can generate an eccentric, high-power electron beam of several 100 keV energy. Highest dose rates and peak-to-valley dose ratios (PVDRs) were achieved for an electron beam impinging perpendicular onto the target surface and a focal spot smaller than the microbeam cross-section. The line-focus X-ray tube simulations demonstrated PVDRs above 20. Conclusion: The line-focus X-ray tube is a suitable compact source for clinical MRT. We demonstrated its technical feasibility based on state-of-the-art high-voltage and electron-beam technology. Microbeam arc therapy is an effective concept to increase the target-to-entrance dose ratio of orthovoltage microbeams.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Compact radiation source; Equivalent uniform dose; Line-focus X-ray tube; Microbeam arc therapy; Microbeam radiation therapy; Modular high-voltage supply